The role of earnings and tax on dividend policy of Indonesian listed firms - Hutagaol-Martowidjojo, Yanthi; Joachim, Hansi; Anggreni, Dellia (Jurnal Keuangan dan Perbankan, 2019)
Prior studies show that profitability is the main financial aspect that determines a firm’s dividend policy. To add to the Indonesian’ dividends literature, this study examines the role of earnings and tax as dividend policy in Indonesian listed firms. This study argues that besides profitability, Indonesian firms consider other financial performance, namely earnings (contributed capital and prior year earnings) and tax to determine their dividend policy, since earnings reflect firm’s real ability to pay dividends, and tax affects the number of dividends should be paid.  Using 1688 firm-year observations of Indonesian firms from 2012 to 2016, the panel data regression result shows that prior year’s earnings and contributed capital, are the significant determinants of firms sample’s dividend policy. However, the insignificant result is found in the corporate tax role. Meanwhile, the robustness test, earnings, and tax are significant and of the expected sign. The result implies that the higher the firms’ earnings, the higher the dividend payout ratio that is used as a proxy to the firms’ dividend policy. Corporate tax, on the other hand, is a significant negative determinant in some years of the observation. Higher corporate tax hinders managers to increase the dividend payout ratio.JEL Classification: G35, M19, M40DOI: https://doi.org/10.26905/jkdp.v23i1.2581